2009
DOI: 10.1111/j.1651-2227.2008.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid content, expression and support of thrombin generation of neonatal platelets

Abstract: Our results do not provide any evidence that a different phospholipid-expression of neonatal platelets may alter TG in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Currently, the neonatal platelet is characterized as hypo -functional as compared to the adult platelet despite evidence of more efficient global primary hemostasis in neonates (5). In this review, the literature regarding neonatal platelet function will be reviewed and synthesized in order to more clearly define the neonatal platelet functional phenotype and its contribution to the newborn’s hemostatic system (Table 1(6-18)).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the neonatal platelet is characterized as hypo -functional as compared to the adult platelet despite evidence of more efficient global primary hemostasis in neonates (5). In this review, the literature regarding neonatal platelet function will be reviewed and synthesized in order to more clearly define the neonatal platelet functional phenotype and its contribution to the newborn’s hemostatic system (Table 1(6-18)).…”
Section: Introductionmentioning
confidence: 99%
“…

Phosphatidylserine (PS) exposure: Annexin V, which binds PS with high affinity, can be used to characterize the procoagulant phenotype of activated platelets. Analysis of PS exposure through measurement of Annexin V binding via flow cytometry has shown that the procoagulant phenotype is similar for both cord blood-derived platelets and adult platelets following stimulation with thrombin (17,18). Along these lines, phospholipid content of adult and cord blood platelets has also been reported to be similar (17,18).

…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phospholipid content and baseline exposure of platelet surface phosphatidylserine is comparable in adults and newborns [65,66]. However, more platelet microparticles are generated and more phosphatidylserine molecules are exposed in the term and preterm platelets when thrombin or calcium ionophores were used as activators [67].…”
Section: Newborn Plateletsmentioning
confidence: 99%
“…To estimate bleeding tendency, is still a diagnostic challenge, particularly for children [8,10,18] . An increasing body of evidence shows that the thrombogram assay as described by Hemker [2,11] may be a useful tool in the diagnosis of hyper-and hypocoagulability . The thrombogram (s. • ▶ Fig.…”
Section: Introduction ▼mentioning
confidence: 99%